How to integrate additive manufacturing technologies into manufacturing systems successfully: A perspective from the commercial vehicle industry - Yi, Li; Gläßner, Christopher; Aurich, Jan C. (Journal of manufacturing systems, 2019)
•Barriers for the integration of additive manufacturing (AM) technologies in the commercial vehicle industry are identified.•A cost model for estimating the manufacturing cost of a build task using selective laser melting is proposed in a cost estimation.•A general procedure and framework to develop a hybrid additive-subtractive process chain has been proposed.•A closed-loop quality control model to realize a long-term product and process quality control with AM is developed.•The developed models and methods have been validated in a use case with industrial partners from the German commercial vehicle industry. Additive Manufacturing (AM) is the umbrella term for manufacturing processes that add materials layer by layer to create parts. AM technologies show numerous potentials in terms of rapid prototyping, tooling and direct manufacturing of functional parts and imply revolutionary benefits for the manufacturing industry. Currently, many industrial areas are marching to a more comprehensive application of AM. Hence, the development of new tools, methods, and concepts for guiding companies to implement AM technologies requires more research attention. This paper introduces the results of a research project carried out by academic and industrial partners from the German commercial vehicle industry. The research project addressed four issues for a long-term application of AM technologies: identification of barriers for AM applications, cost estimation for AM application, design of hybrid additive-subtractive process chains, and quality management with AM.